Analisis Determinan Kepuasan Pasien di Rumah Sakit Pelita Anugerah Demak - Aprih Santoso; Yunita Noviasari; Sri Yuni Widowati (Neolectura, 2020)
The purpose of this study was to determine the effect of service quality, location and trust on Outpatient satisfaction at Pelita Anugerah Demak Hospital. The object of this research is PELITA ANUGERAH HOSPITAL DEMAK. The hypothesis of this study is the effect of service quality, location, and trust on outpatient satisfaction.The population of this study was known as 2,300 outpatients. The sample used in this study was 96 respondents using purposive sampling technique, which is a sampling technique that provides the opportunity to become a sample member with certain criteria. Methods of data collection through questionnaires and data analysis using SPSS version 22 which includes the validity test, reliability test, t test, F test and R2 test.The results of this study indicate that all independent variables, namely Service Quality (X1), Location (X2) and Trust (X3) have a positive and significant effect on Outpatient Satisfaction (Y). Based on the coefficient of determination of 0.552 it is known that in this study Service Quality, Location, and Trust affect the Outpatient Satisfaction of 55.2% while the remaining 44.8% is influenced by other variables not explained in the study.